Contracts as a Barrier to Entry - Aghion, Philippe; Bolton, Patrick (American Economic Review, 1987)
It is shown that an incumbent seller who faces a threat of entry into his or her market will sign long-term contracts that prevent the entry of some lower-cost producers even though they do not preclude entry completely. Moreover, when a seller possesses superior information about the likelihood of entry, it is shown that the length of the contract may act as a signal of the true probability of entry.